Genetic and genomics in congenital heart disease: a clinical review - Aline Saliba; Ana Carolina Vaqueiro Figueiredo; José Eduardo Baroneza; Jorge Yuseff Afiune; Aline Pic‐Taylor; Silviene Fabiana de Oliveira; Juliana Forte Mazzeu (Brazilian Society of Pediatrics, 2020)
Objective: Discuss evidence referring to the genetic role in congenital heart diseases, whether chromosomic alterations or monogenic diseases. Data source: LILACS, PubMed, MEDLINE, SciELO, Google Scholar, and references of the articles found. Review articles, case reports, book chapters, master's theses, and doctoral dissertations were included. Summary of findings: Congenital heart diseases are among the most common type of birth defects, afflicting up to 1% of the liveborn. Traditionally, the etiology was defined as a multifactorial model, with both genetic and external contribution, and the genetic role was less recognized. Recently, however, as the natural evolution and epidemiology of congenital heart diseases change, the identification of genetic factors has an expanding significance in the clinical and surgical management of syndromic or non‐syndromic heart defects, providing tools for the understanding of heart development. Conclusions: Concrete knowledge of congenital heart disease etiology and recognition of the genetic alterations may be helpful in the bedside management, defining prognosis and anticipating complications. Resumo: Objetivo: Discutir as evidências referentes ao papel genético em cardiopatias congênitas, sejam alterações cromossômicas ou doenças monogênicas. Fonte de dados: Lilacs, PubMed, Medline, SciELO, Google Scholar e referências dos artigos encontrados. Artigos de revisão, relatos de casos, capítulos de livros, dissertações de mestrado e teses de doutorado foram incluídos. Síntese dos dados: As cardiopatias congênitas estão entre os tipos mais comuns de defeitos congênitos, afetando até 1% dos nascidos vivos. Tradicionalmente, a etiologia era definida como um modelo multifatorial, com contribuição tanto genética quanto externa, sendo o papel genético menos reconhecido. Recentemente, no entanto, à medida que a evolução natural e a epidemiologia das cardiopatias congênitas mudaram, a identificação de fatores genéticos tem adquirido importância crescente no tratamento clínico e cirúrgico de defeitos cardíacos sindrômicos e não-sindrômicos, fornecendo ferramentas para a compreensão do desenvolvimento do coração. Conclusões: O conhecimento concreto da etiologia das cardiopatias congênitas e o reconhecimento das alterações genéticas podem ser úteis no tratamento à beira do leito, definindo o prognóstico e antecipando as complicações.